Prolactin-releasing peptide improved leptin hypothalamic signaling in obese mice - Holubová, Martina; Hrubá, Lucie; Neprašová, Barbora; Majerčíková, Zuzana; Lacinová, Zdeňka; Kuneš, Jaroslav; Maletínská, Lenka; Železná, Blanka (Journal of molecular endocrinology, 2018)
The situation following anti-obesity drug termination is rarely investigated, eventhough a decrease in body weight needs to be sustained. Therefore, this study examined the impact of twice-daily peripheral administration of 5 mg/kg [N-palm-γGlu-Lys11] prolactin-releasing peptide 31 (palm11-PrRP31) in mice with diet-induced obesity (DIO from consuming a high-fat diet) after 28 days of treatment (palm11-PrRP31 group) and after 14 days of peptide treatment followed by 14 days of discontinuation (palm11-PrRP31 + saline group). At the end of the treatment, cumulative food intake, body weight and subcutaneous fat weight/body weight ratio and leptin plasma level were reduced significantly in both the palm11-PrRP31 group and the palm11-PrRP31 + saline group compared to the saline control group. This reduction correlated with significantly increased FOSB, a marker of long-term neuronal potentiation, in the nucleus arcuatus and nucleus tractus solitarii, areas known to be affected by the anorexigenic effect of palm11-PrRP31. Moreover, activation of leptin-related hypothalamic signaling was registered through an increase in phosphoinositide-3-kinase, increased phosphorylation of protein kinase B (PKB, AKT) and enhanced extracellular signal-regulated kinase 1/2 phosphorylation. Besides, lowered apoptotic markers c-JUN N-terminal kinase and c-JUN phosphorylation were registered in the hypothalami of both palm11-PrRP31-treated groups. This study demonstrates that palm11-PrRP31 positively affects feeding and leptin-related hypothalamic signaling, not only after 28 days of treatment but even 14 days after the termination of a 14-day long treatment without the yo-yo effect.
Keywords: Animals; Mice, Obese; Eating; apoptóza; Apoptosis; Organ Size; Leptin; lidé; neurony; signální transdukce; messenger RNA; Receptors, Leptin; Signal Transduction; přijímání potravy; myši obézní; Prolactin-Releasing Hormone; RNA, Messenger; omezení příjmu potravy; Neurons; leptin; Hypothalamus; velikost orgánu; fosforylace; myši inbrední C57BL; Male; hypothalamus; leptinové receptory; zvířata; mužské pohlaví; Fasting; Mice, Inbred C57BL; Phosphorylation; hormon uvolňující prolaktin; Humans